The Legitimation Construction in Regent of Garut’s Statements on His Unregistered Marriage: A Critical Discourse Analysis - Prita Annisa Utami (Universitas Pendidikan Indonesia (UPI), 2013)
Legitimation is one form ofthe social actionswhichis often done eventhough it isprobably less recognized. The present study examines the legitimation construction by the Regent of Garut and also the ideologies underlying the legitimation. It uses van Leeuwen’s (2008) framework regarding discursive construction of legitimation under the theory of Critical Discourse Analysis. This study is largely qualitative, but some quantification is employed to support the description. The collected data are in the form of statements delivered by Regent of Garut related to his unregistered marriage to a young girl. The data are analyzed in the unit of clause to reveal the legitimation construction in the texts. This study finds that from four major types of legitimation asserted by van Leeuwen (2008),only three types of legitimation are evidenced in the texts, i.e. rationalization (44.44%), authorization (44.44%), and moral evaluation (11.11%). Hence, the Regent of Garut’s actions in the texts are strongly legitimized through the logical explanation to support the unregistered marriage, supported by referring to high status as the basis of the actions, and the reference to moral value of humanity to avoid adultery. The ideologies underlying the legitimation are feudalism and masculinism.Keywords: Critical Discourse Analysis, Legitimation, Regent Of Garut, Unregistered Marriage, Ideology.